Analysis and Optimization of automotive seat structure based on finite element method. Issue 1 (October 2020) - Dongliang, Geng; Fengling, Gao; Xiaobing, Bu; Bayi, Yu; Tang, Yan; Yuan, Wu
Abstract: According to the rigid design standard of automotive seat frame structure, the strength and stiffness of a vehicle seat is analyzed and optimized in this paper. The finite element analysis results show that the initial design of the seat can basically meet the stiffness requirements under most standard test conditions. However, in the front crash test condition, there is a risk of strength failure in the seat rail. Therefore, it is necessary to optimize the structure. Based on the engineering experience, local characteristics of the seat rail is modified. After conducting simulation of the improved seat structure, it is demonstrated that the seat meets all the design requirements of stiffness and strength.